2019
DOI: 10.3389/fpsyt.2019.00369
|View full text |Cite
|
Sign up to set email alerts
|

Negative Life Events and Problematic Internet Use as Factors Associated With Psychotic-Like Experiences in Adolescents

Abstract: Objectives: Psychotic-like experiences (PLEs) and problematic internet use (PIU) are common in adolescents. However, little is known about the association between PLEs and PIU among adolescents. The present study examined the associations between PLEs and PIU and negative life events among adolescents. Methods: In total, 1,678 adolescents attending high school were recruited for a cross-sectional survey. They completed self-reported assessments of PLEs using the Prodromal Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…Being bullied has been associated with anxiety and depression symptoms ( 7 ), with having more severe mental health problems ( 8 ), and with an increased risk of suicidal ideation ( 9 ). Moreover, the risk of psychotic-like experiences in adolescents may be increased by the number of traumatic events experienced—including bullying ( 10 ). Wu et al ( 11 ) focused on the consequences of bullying on mental health depending on the role and found that these consequences are more important for victims and bystanders than for bullies.…”
Section: Introductionmentioning
confidence: 99%
“…Being bullied has been associated with anxiety and depression symptoms ( 7 ), with having more severe mental health problems ( 8 ), and with an increased risk of suicidal ideation ( 9 ). Moreover, the risk of psychotic-like experiences in adolescents may be increased by the number of traumatic events experienced—including bullying ( 10 ). Wu et al ( 11 ) focused on the consequences of bullying on mental health depending on the role and found that these consequences are more important for victims and bystanders than for bullies.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of major life events put a lot of pressure on an individual, leading to many psychological problems and challenges ( 19 ). Anxiety and depressive symptoms are the most common mental problems of adolescents and young adults ( 20 ), which are generally caused by negative life events and a lack of social support ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that IAD is closely related to negative events experienced by individuals [17,20,35,36]. In addition, healthy adaptation, punishment, interpersonal relationship and learning pressure factors are the dimensions that predict a high degree of IAD in life events [16,18,30,37].…”
Section: Discussionmentioning
confidence: 99%